2014
DOI: 10.1089/jpm.2013.0569
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Spiritual Needs of Patients with Advanced Cancer in a Palliative Care Unit

Abstract: When patients knew the truth about their illnesses and they were treated with dignity, their most important needs were likely to be covered. These results suggest that patients receiving palliative care wish to live for the present with as much normality as possible and show only minor concern for their past and future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
64
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 15 publications
3
64
0
6
Order By: Relevance
“…A study indicated that the nurses were able to identify the patients' spiritual needs and strategies to meet them, but further research is needed since spiritual suffering may manifest as psychological symptoms such as anxiety, anguish, and depression (3) . Spiritual needs are also characterized as being recognized as a person to the end of life, the need for the truth, reinterpreting life, recognizing the meaning of life, hope, and religious expression (19) .…”
Section: Resultsmentioning
confidence: 99%
“…A study indicated that the nurses were able to identify the patients' spiritual needs and strategies to meet them, but further research is needed since spiritual suffering may manifest as psychological symptoms such as anxiety, anguish, and depression (3) . Spiritual needs are also characterized as being recognized as a person to the end of life, the need for the truth, reinterpreting life, recognizing the meaning of life, hope, and religious expression (19) .…”
Section: Resultsmentioning
confidence: 99%
“…Self‐blame was found positively associated to DR‐ED, providing useful evidence to detect the variables that can lead to a clinically relevant degree of existential distress. Furthermore, end‐of‐life patients, who do not share their illness‐related relevant concerns, are more likely to blame themselves, which can lead to an increased risk of depressive symptoms …”
Section: Discussionmentioning
confidence: 99%
“…Intervention participants showed improvements in functional status, anxiety, depression, and preparation for end-oflife [50,62]. Concerning the need to reinterpret a person's life, it was observed that patients tended to make a positive and significant revision of their past, which helped them recover their selfesteem [83].…”
Section: Reviewmentioning
confidence: 98%